Adhesion, roughness, wettability, and dielectric strength of elastomers liquid blends for high-density fiberboard wood adhesive - Hussein, Seenaa; Maha K. Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the present study, the physical characteristics of elastomer (EL) blend with natural polymers such as polyvinyl alcohol (PVA), Dexrin (D), Arabic gum (AG), and corn starch (CS) based on high-density fiberboard wood adhesives were investigated. The EL blends were prepared by dissolving AG, D, PVA, and CS in deionized water at 70 °C for 1 h under magnetic stirring continuously until the solution was clear, and blends were made with a weight of 60/40 (w/w); then were cast into a mold with a 20 cm diameter and left at room temperature for 24 h to ensure complete water removal and drying of the samples. The prepared EL and EL blend structures, adhesion strengths, roughness, wettings, and dielectric strengths, were investigated. The modified EL blend reveals a 144 MPa for pull-off strength and 770.8 N for shear strength for high-density fiberboard (HDF) wood as a substrate to the EL/AG, respectively. The surface roughness and contact angle of the EL/PVA mixture were found to be high, measuring 4.57 µm for roughness and shows the water contact angles for the samples. An increase in the contact angle of the El/AG blend where reached to(83.94˚) was observed due to the decrease in the –COOH and OH groups present in the backbone of the arabic gum. The greatest dielectric strength for EL/AG was reported to be 18.62 kV/mm at 0.5 kV/s and 22.77 kV/mm at 5 kV/s.and optical microscoby image for break down region was shown the carbonization in the break down point as aresult of carashing polymers chains, also micro cracks occuring forspecimens and this cracks extends directly from the breakdown region